Badanie napływu inwestycji zagranicznych do Polski z wykorzystaniem metod wielowymiarowej analizy porównawczej - Lewandowska, Karolina (An Application of Multi-Scale Comparison Analysis in the Study of the Flow of Foreign Investments to Poland, 2007)
The article presents results of spatial analysis of foreign investments location in Poland. In the first part of this study, methods of multi-scale comparison analysis were used for classification of Polish districts according to location competitiveness for foreign investments. In the second part, the same methods were used for grouping of Polish districts according to the amount of finalized investments in analyzed period of time. Publication of GUS, NBP and PAIZ served as sources of statistical data used in this study.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 376-384